Financial and Non-Financial Compensation on Employee Productivity - Huda, Jaya Alfian; Akbar, Mohammad Aldrin; Lina, Ros (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the effect of financial and non-financial compensation on employee productivity at Bank Papua, Abepura Branch. Using reinforcement theory and expectancy theory, it investigates how both forms of compensation affect employee motivation and performance. Research Design and Methodology: This study utilized a quantitative approach, using surveys and statistical analysis to assess the relationship between compensation and productivity. Data was collected from employees at the Abepura Branch of Bank Papua. Both financial compensation (e.g., salary, bonus) and non-financial compensation (e.g., recognition, career development opportunities) were measured and analyzed for their impact on employee productivity. Findings and Discussion: The findings show financial and non-financial compensation's vivacious and significant effect on employee productivity. The findings are consistent with motivation and fairness theories, indicating that fair and competitive compensation encourages employees to work harder and perform better. The discussion emphasizes the importance of a balance between both forms of compensation to improve overall productivity and organizational performance. Implications: This research highlights practical implications for management at Bank Papua, Abepura Branch. It indicates the need for greater attention to the compensation structure to ensure employee satisfaction and motivation. Recommendations include periodic salary reviews and adjustments, developing incentive programs based on individual and team performance, and creating a supportive work environment.